Meningkatkan Hasil Belajar Kayang Melalui Metode Latihan Pada Siswa Kelas XII SMA Negeri 16 Seram Bagian Barat - Tarmon, Umar; Fenanlampir, Albertus; Matitaputty, Johana (Peneliti.net, 2024)
This research was motivated by the low interest of students in Kayang floor exercise material in class XII of SMA Negeri 16 Seram Barat. This condition is caused by teachers' habits of applying conventional models and lecture methods, not facilitating students with relevant learning resources, in addition to the methods applied during learning, students tend to get bored and not focused during the learning process, so that students always find it difficult to understand concepts. material studied. This results in students feeling bored and it is feared that it could affect students' cognitive abilities. The application of the Training Method can be used as an alternative solution to overcome the low Kayang Learning Results. This research was carried out over two cycles with Classroom Action Research (PTK) procedures following the Kemmis and McTagart scheme, namely planning, action, evaluation and reflection. The subjects of this research were 20 class XII students of SMA Negeri 16 West Seram for the 2022/2023 academic year. Data collection techniques were taken through interviews, observation, and learning outcomes tests. Data analysis was carried out descriptively qualitatively through interviews and observations. The research results showed that the percentage of students' Kayang learning outcomes increased from cycle I to cycle II actions. During 2 cycles, in cycle I student completion was 30%, while cycle II had completion at 95%, so it can be concluded that there was a significant increase in Kayang's learning outcomes through the training method.